Предмет: Алгебра,
автор: Аноним
Помогите плиз. Номер 28.24 а) Help!!
Приложения:
Ответы
Автор ответа:
0
(x+2)^2 * (x-5)^3 = (х-5) * (x+2)^4
можно сократить и получится, что (х+2)^2 сократятся и получится
(x-5)^3 = (х-5)
(х-5)^2=(х+2)^2
x^2 - 10x + 25 =x^2+4x+4
-14x-21=0
-14x=21
x=21/-14
x=-3/2=-1.5
можно сократить и получится, что (х+2)^2 сократятся и получится
(x-5)^3 = (х-5)
(х-5)^2=(х+2)^2
x^2 - 10x + 25 =x^2+4x+4
-14x-21=0
-14x=21
x=21/-14
x=-3/2=-1.5
Похожие вопросы
Предмет: Математика,
автор: anjalichtin
Предмет: Литература,
автор: kovsarovatatana39
Предмет: Русский язык,
автор: ocenka0715
Предмет: Информатика,
автор: Аполлинария1818
Предмет: Математика,
автор: Tamiris9